Energy pathways modulate the resilience of stream invertebrate communities to drought. Issue 9 (17th April 2021) - Nelson, Daniel; Busch, Michelle H.; Kopp, Darin A.; Allen, Daniel C.
Abstract: While climate change is altering ecosystems on a global scale, not all ecosystems are responding in the same way. The resilience of ecological communities may depend on whether food webs are producer‐ or detritus‐based (i.e. 'green' or 'brown' food webs, respectively), or both (i.e. 'multi‐channel' food web). Food web theory suggests that the presence of multiple energy pathways can enhance community stability and resilience and may modulate the responses of ecological communities to disturbances such as climate change. Despite important advances in food web theory, few studies have empirically investigated the resilience of ecological communities to climate change stressors in ecosystems with different primary energy channels. We conducted a factorial experiment using outdoor stream mesocosms to investigate the independent and interactive effects of warming and drought on invertebrate communities in food webs with different energy channel configurations. Warming had little effect on invertebrates, but stream drying negatively impacted total invertebrate abundance, biomass, richness and diversity. Although resistance to drying did not differ among energy channel treatments, recovery and overall resilience were higher in green mesocosms than in mixed and brown mesocosms. Resilience to drying also varied widely among taxa, with larger predatory taxa exhibiting lower resilience. Our results suggest that the effects of drought on stream communities may vary regionally and depend on whether food webs are fuelled by autochthonous or allochthonous basal resources. Communities inhabiting streams with large amounts of organic matter and more complex substrates that provide refugia may be more resilient to the loss of surface water than communities inhabiting streams with simpler, more homogeneous substrates. Abstract : On a global scale, ecosystems are changing at an unprecedented rate due to climate change. However, not all ecosystems are responding equally, as ecosystems can vary in their resilience to disturbances. The authors tested whether food web energetic pathways can modulate the effects of climate change on stream communities. They found that producer‐dominated food webs may be more resilient to drought than detritus‐dominated food webs.